2020
DOI: 10.18047/poljo.26.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Utjecaj gustoće sjetve na prinos zrna i komponente prinosa jaroga stočnog graška

Abstract: The spring field pea is one of the most important coarse legumes. This study was carried out to investigate the response of a spring field pea variety to three plant densities (50, 100, and 150 plant m-2) during the 2017 and 2019 growing seasons in eastern Croatia. The field study was set up as a Randomized Complete Block Design (RCBD) in four replications. The results have demonstrated a significant effect of the plant densities and the growing seasons on the seed yield and on the following yield components: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…GUGAŁA andZARZECKA [2009] andTÜRK et al [2011] obtained the highest yield from the planting stock of 125-150 pcs.•m -2 , and the lowest from the planting density of 75 pcs.•m -2 . KRIZMANIĆ et al [2020] found that sowing peas at different densities significantly modified the seed yield, plant height, and the number of pods per plant, and did not affect the number of seeds in a pod or the weight of 1000 seeds. SPIES et al…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…GUGAŁA andZARZECKA [2009] andTÜRK et al [2011] obtained the highest yield from the planting stock of 125-150 pcs.•m -2 , and the lowest from the planting density of 75 pcs.•m -2 . KRIZMANIĆ et al [2020] found that sowing peas at different densities significantly modified the seed yield, plant height, and the number of pods per plant, and did not affect the number of seeds in a pod or the weight of 1000 seeds. SPIES et al…”
Section: Resultsmentioning
confidence: 92%
“…In own research, the most seeds were also obtained from plants at a similar plant density (70 pcs.•m -2 ) -Table 5. KRIZMANIĆ et al [2020] stated instead the planting density per m 2 had no significant effect on the number of pods or the number of seeds per plant; SALTER and WILLIAMS [2015] observed in their research that the weight of pea seeds systematically decreased with increasing planting density. Similarly, in this study, a decrease in seed weight per plant with an increase in seeding density and row spacing was noted (Tab.…”
Section: Resultsmentioning
confidence: 97%
“…The seed drill was operated in the field under different working speeds; all the seeds from each plastic packet were collected, the seeds damaged were counted and weighted, and the percentage of the seeds damaged was calculated, as follows in Eq. (12).…”
Section: Measurements On the Crop Growthmentioning
confidence: 99%
“…Pea (Pisum sativum L.) is one of the extremely crucial legume species (Krizmanić et al, 2020); it is a fundamental source of high-quality proteins, micronutrients, starch, phenolic compounds, dietary fibers, and antioxidants (Yu et al, 2021). Pea seeds are smooth or wrinkled; the weight of 100 seeds ranges from 10 to 36 g. Pea plants up to 80 per square meter at 3 to 5 cm depth, about 10 cm apart in rows (Garden peas production, 2011).…”
Section: Introductionmentioning
confidence: 99%